A Comparison of Consumptive Behavior Between the Younger Generation and Housewives in the Digital Era - Raycila Agita Putri; Alna Hanana (Talenta Publisher, 2026)
This study compares consumptive behavior between the younger generation and housewives in the digital era and analyzes how digital culture shapes their shopping patterns. The rapid development of social media, e-commerce platforms, and digital marketing has shifted consumption from fulfilling basic needs toward lifestyle expression, trends, and social identity. This research provides a sociological perspective on how social roles and digital exposure influence differences in consumption behavior. The study uses a small-scale qualitative exploratory approach involving two informants: a college student representing the younger generation and a housewife representing domestic consumers. Data were collected through semi-structured interviews and observation, then analyzed using thematic analysis focusing on impulse buying, social media influence, financial management, and shopping motivation. The findings indicate that the younger generation tends to exhibit more impulsive buying behavior, driven by social media trends, influencer content, online promotions, and algorithm-based recommendations. In contrast, housewives demonstrate more controlled consumption patterns, prioritizing household needs, budgeting, and practical considerations, although they also actively use online shopping platforms. Overall, consumptive behavior in the digital era is shaped not only by technological exposure but also by social roles, economic responsibility, and lifestyle orientation. Despite the limited number of participants, this study offers exploratory insights into how digital platforms influence consumption practices and everyday decision-making in different social groups.